Analysis of The Good Corporate Governance Effect on Profitability in Registered Manufacturing Companies in Indonesia Stock Exchange - Sutri Handayani (Journal of Economics, Business, and Government Challenges, 2019)
This study aimed to find out the effect of Good Corporate Governance toward profitability of listed manufacturer companies in Indonesian stock exchange in 2012-2016 periods. The proxies of Good corporate governance are board of commissioners, board of directors, and audit committee. Moreover, the profitability is measured by Return On Equity (ROE). Population in this study were registered manufacturer companies in Indonesian stock exchange in 2012-2016 periods. The sampling technique is purposive sampling method. Based on this method, it is obtained 29 companies. The type of data is secondary data. The data processing uses SPSS (Statistical Package for Social Science) v.20. The data analysis technique used multiple linear regressions. The result of this study showed that partially, the Board of Commissioners and the Audit Committee have no significant effect on profitability while the Board of Directors has a significant influence on profitability. Simultaneously the Board of Commissioners, the Board of Directors, and the Audit Committee had a significant influence on profitability.